New locality records and echolocation call description of pouched bat (Saccolaimus saccolaimus) (Chiroptera Emballonuridae) from the Philippines - Duco, Renz Angelo J. (Philippine Journal of Science, 2023)
Echolocation call descriptions of local bat species in the Philippines have been published recently. However, collected reference call data has been biased towards species that can easily be captured using mist nets and harp traps, whereas acoustic data for rare and aerial species that are less frequently recorded by traditional means remain absent. Significant gaps still exist in our knowledge about the distribution, ecology, behavior, and population of most of these high-flying bats in the Philippines. In this study, we report new locality records and provide an echolocation call description for Saccolaimus saccolaimus, a locally rare bat species with only a few known records from the Philippines. Three localities surveyed represent new distributional records for this species in the Philippines: La Union and Bulacan in Luzon Island, and Davao City in Mindanao Island. Echolocation calls of this species are mainly characterized by pulses of long multi-harmonic calls, which are emitted at ca. 20 kHz, the lowest frequency recorded thus far among Philippine bats. Our data contributes to understanding this species’ distribution and preference for modified habitats and residential areas, as well as to providing reference call data for future acoustic surveys and monitoring of this rare bat species.